Socio-ecological dynamics of a tropical agricultural region: Historical analysis of system change and opportunities. (February 2019) - Antoni, Carolin; Huber-Sannwald, Elisabeth; Reyes Hernández, Humberto; van't Hooft, Anuschka; Schoon, Michael
Highlights: With the adaptive cycle as a heuristic tool, we identified key development phases of the LM-SES and the triggers of system phase and state changes. The social and socio-ecological resilience undergoes frequent changes. Changes in land property and land use policies were key drivers of internal transformations of the LM-SES. Abstract: Land use change arises from a variety of socio-economic and/or biophysical drivers, with direct and/or indirect feedbacks on the long-term functionality of the land as the fundamental life-support system for human wellbeing. Understanding the spatiotemporal dynamics of production systems is critical for decision-making to maintain both functioning ecosystems and land-dependent livelihoods. We applied the adaptive cycle metaphor to examine historic spatiotemporal changes in one of the largest communal regions ( ejido ) in the Northern most extension of the tropical forest biome in Mexico. This large-scale case study explores the effects of a series of exogenous and endogenous drivers that transformed a former dense tropical forest into an intensive industrial sugarcane plantation with parallel developments and adjustments of rural livelihoods. We demonstrate how integral knowledge on the historical development of a 70-year old social-ecological system (SES) helps build fundamental understanding of the vulnerability, resilience, and adaptability of land and people (livelihoods) to current diverse external and endogenous drivers. With the adaptive cycle metaphor, we identified stable system states and the current phase of our focal SES, which, before the 1940s, was covered by dense dry tropical forest. The current SES had passed all phases in the adaptive cycle more than once and is presently in the early conservation phase represented by a high input commercial sugarcane production system with reduced resilience to external drivers of change. We show which drivers and historical events best explained the regional socio-ecological system dynamics including its vulnerability, resilience, and adaptability considering certain system states. Understanding system dynamics and phase changes considering the adaptive cycle metaphor helps identify both social and ecological resilience characteristics, and unexplored windows of opportunity for guided transformation of system states out of social-ecological traps.